Pengaruh Elastic Band Exercise terhadap Penurunan Tekanan Darah pada Lansia - Oktaviani, Vernanda; Fahri, Ana Mustafiyah; Asyhari, Atge Oktoreza; Kusumawati, Yoni Rustiana (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: High blood pressure or commonly known as hypertension is a non-curable disease characterized by systolic pressure ≥140 mmHg and diastolic pressure ≥90 mmHg. Exercise is a non-pharmacological treatment that has a significant effect in lowering blood pressure and exercise can be done by anyone because it is easy. Physiotherapy plays a role in providing elastic band exercise (EBE) which is one of the exercises that can improve muscle strength, body composition, and cardiovascular fitness in the elderly. When someone does exercise, there is a decrease in activity in the sympathetic nerves and the parasympathetic nerves experience an increase in activity, which causes the body to automatically respond to a decrease in blood pressure. Objectives: To determine the effect of elastic band exercise on lowering blood pressure in the elderly. Methods: The subjects in this study were 30 members of the Elderly Posyandu (Poslan) in Tohudan Hamlet, Colomadu Karanganyar. The inclusion criteria in this study are as follows: (1) subjects aged 60-79 years (2) hypertension with systolic pressure ≥140 mmHg and/or diastolic pressure ≥90 mmHg, (3) communicate well and are able to follow the instructions given (4) willing to participate in the study by signing an informed consent. This study is a pre-experimental study, the research design uses a one group pre-post test design, namely one group of elderly people who will be given treatment in the form of elastic band exercise. Results: The results of the difference in the effect of pre-test and post-test on research subjects using the Wilcoxon Test obtained results for systole p = 0.00 (p <0.05) and diastole p = 0.00 (p <0.05). This shows the influence of research subjects on reducing blood pressure in the elderly. Conclusion: Providing elastic band exercise has an effect on reducing blood pressure in the elderly. Keywords: Elastic band exercise, Blood pressure, Elderly, Hypertension.